Improving Profitability through Value Engineering: A Case study - Desai, Darshak A. (Asian Journal of Engineering and Applied Technology, 2012)
Value Engineering is a function-oriented technique that has proven to be an effective management tool for achieving improved design, construction, and cost-effective solution for many engineering problems. It is one of the most effective techniques known to identify and eliminate unnecessary costs in product design, testing, manufacturing, construction, operations, maintenance, procedures and practices. This paper is an attempt to highlight the application of value engineering techniques towards profitability improvement. The paper discusses a case of fabrication industry mainly dealing with different security cabinets. The paper illustrates how the value engineering efforts resulted into the positive impact on the profitability of the company.